A taxonomic revision of Neobuprestis Kerremans (Coleoptera : Buprestidae) with the description of a new genus and two new species - Levey, B.; Bellamy, C. L. (Zootaxa, 2013)
The genus Neobuprestis Kerremans 1903 is redefined and a new genus Burnsiellus gen. n. is defined. The putative rela-tionships of Neobuprestis and Burnsiellus gen. n. are discussed. A key to the species of the two genera are provided. Bal-thasarella Obenberger 1958 is made a subgenus of Neobuprestis and its type species B. melandryoides Obenberger 1958 is synonymised with Strigoptera frenchi Blackburn 1892. Strigoptera marmorata Blackburn (1892), Neobuprestis albos-parsa Carter (1924), Neobuprestis trisulcata Carter (1932) are transferred to Burnsiellus gen. n. from Neobuprestis.Two new species are described: Neobuprestis (Balthasarella) williamsi sp. n., Burnsiellus lobatum sp.n.